Just a summer romance - Martin, Ann M., 1955- (New York : Scholastic, 1988)
Fourteen-year-old Melanie can't forget the handsome, mysterious boy who was her "summer romance," and when she sees his face on the cover of "People" magazine, she is determined to learn the truth about him.
6.1
Young Adult
Young Adult
School Library Journal
Booklist
Keywords: Love -- Fiction; Love stories